K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 6 2020

\(P\left(x\right)=3x^5+x^4-2x^2+2x-1\)

\(Q\left(x\right)=-3x^5+2x^2-2x+3\)

\(P\left(x\right)+Q\left(x\right)=3x^5+x^4-2x^2+2x-1-3x^5+2x^2-2x+3\)

\(=x^4+2\)

\(P\left(x\right)-Q\left(x\right)=3x^5+x^4-2x^2+2x-1+3x^5-2x^2+2x-3\)

\(=6x^5+x^4-4x^2+4x-4\)

7 tháng 6 2020

Thu gọn + sắp xếp luôn

P(x) = 3x5 + x4 - 2x2 + 2x - 1

Q(x) = -3x5 + 2x2 - 2x + 3

P(x) + Q(x) = ( 3x5 + x4 - 2x2 + 2x - 1 ) + ( -3x5 + 2x2 - 2x + 3 )

                   = ( 3x5 - 3x5 ) + x4 + ( 2x2 -- 2x2 ) + ( 2x - 2x ) + ( 3 - 1 )

                   = x4 + 2

P(x) - Q(x) = ( 3x5 + x4 - 2x2 + 2x - 1 ) - (  -3x5 + 2x2 - 2x + 3 )

                  = 3x5 + x4 - 2x2 + 2x - 1 + 3x5 - 2x2 + 2x - 3

                  = ( 3x5 + 3x5 ) + x4 + ( -2x2 - 2x2 ) + ( 2x + 2x ) + ( -1 - 3 )

                  = 6x5 + x4 - 4x2 + 4x - 4